Human Resource Management and Mosque Performance: A SMART-PLS - Asfia, Asfa; Herindar, Evania; Azqia, Hidayatul (The Economic Review of Pesantren, 2023)
Along with the development of times and problems in an increasingly complex society, demanding the mosque must improve its performance and role concretely. Youth has a very important role in improving the performance of a mosque. The purpose of this study is to analyze the variable Strategic Human Resource Management (SHRM) and sharia financial literacy on mosque performance at the Al-Lathiif mosque in Bandung. This study used a sample of 82 respondents from the Hijrah youth community (Shift) drawn based on a purposive sampling technique. The analytical method in this study uses Structural Equation Modeling (SEM). The results showed that the value of R2 in the dependent construct in this study showed a value of 0.462 which means that the latent variable of mosque performance can be influenced by strategic human resource management simultaneously and sharia financial literacy by 46.2%, while the rest is influenced by other variables not examined in this research model. Meanwhile, SHRM with a value of 2.128 and a coefficient value of 0.012 has no significant effect because this research found that the Al lathiif mosque has not implemented SHRM formally and thoroughly. Likewise, Islamic financial literacy is influential but not significant to mosque performance.